PENINGKATAN POTENSI DESA TANJUNGKENONGO KECAMATAN PACET KABUPATEN MOJOKERTO MENUJU DESA WISATA - Al Hamzah, M. Habibie; Prasetyo, M. Roby (Jurnal ABDI Bhayangkara, 2020)
The development of technology and information systems in this era is very helpful in increasing the pace of the economy. The fact, in rural areas still minimal use of technology and internet-based information systems to help marketing their products. Traditional marketing is a tool that they still use, by selling their products to broker’s or waiting for buyers to buy their product. Therefore, we want to focus more on improving the quality of human resources in Tanjungkenongo Village through activities, such as (1) Counseling on technology-based marketing methods through applications such as WA, IG, and Facebook. (2) Counseling on packaging and branding methods so the product becomes more attractive (3) Planting tabebuya seeds to improve the aesthetics of Tanjungkenongo Village in the future (4) Provision of chili, tomato, and moringa seeds to Tanjungkenongo villagers in order to benefit the residents in the future. The counseling of the above activities was carried out for PKK communities in Tanjungkenongo Village, with the aim that they could make the most of the potential of natural resources in Tanjungkenongo Village.